Envolvimento e educação ambiental com as quebradeiras de coco: um caminho sustentável na reserva extrativista do extremo norte do Tocantins - Vieira, Fábio Pessoa (Universidade Federal do Tocantins, 2018)
This thesis sought to investigate an existential conception of Environmental Education, having as support the sustainable way. The aim was to make a critique, the way in which the concept of sustainable development is imposed in a homogenous and hegemonic form in Environmental Education. To do so, we present the sustainable way, constituted from environmental involvement, which in turn is woven by a struggle for self-sufficiency, for environmental conservation and for social justice, in a construction based on the place. Therefore, to think of environmental involvement is to understand that there is a diversity of human experiences based on the relationship of intimacy and belonging that certain native communities have with the place and nature. In this work, the knowledge and experiences of the extractivists of the extractive reserve of the extreme North of Tocantins are what underpin environmental involvement. The decolonial, and post-colonial perspectives and phenomenology theoretically and epistemically ground the plot of the thesis. Phenomenology is also the method for the pursuit of research, focusing on its humanistic understandings, beyond the existential research-action technique and document-analysis. As results, we present that the relationships between humans towards their peers and with nature, exposed in the essentials of the sustainable way and existing in the extractive reserve of the extreme North of Tocantins, break with the thought produced by modern-colonial society that imposes a only way to be sustainable. Therefore, from the results obtained, we highlight that in the daily life of native communities, with the essences of the sustainable way, allied to a dialogue of knowledge, is the foundation of existential Environmental Education.